STRATEGY MANAGEMENT OF INSTAGRAM @SUROBOYOBUS TO INCREASE AWARENESS OF PUBLIC TRANSPORTATION IN SURABAYA CITY SOCIETY - Nabila, Rahmania; Sukardani, Puspita Sari (The Commercium, 2022)
With the presence of social media now, it gave birth to a low budget high impact marketing concept. Instagram is in demand by agencies or companies as a medium to increase engagement in achieving brand awareness in their market target. This study aims to determine the strategy of managing instagram @suroboyobus social media in increasing brand awareness, especially in the people of Surabaya City. For this reason, this research uses a qualitative descriptive approach with a case study method. The method of collecting data by interviewing 4 informants consisting of UPTD PTU staff who are the managers of Suroboyo Buses, e-Dishub staff who act as admins or managers of @suroboyobus instagram accounts, and instagram followers who are also as a Suroboyo Bus passengers. Based on the results of interviews, documentation, and observations, the management strategy of nstagram @suroboyobus use the communication model The Circular Model of SoMe initiated by Regina Lutrell. This model is divided into four parts, namely: Share, Optimize, Manage, and Engage. Strategies in increasing public transportation awareness through the selection of more informative content are considered to be able to increase the engagement of followers and other Instagram users. Keywords : Management Instagram, Suroboyo Bus, Brand Awareness